2020
DOI: 10.1049/iet-nbt.2019.0210
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic cobalt ferrite nanoparticles as T 2 contrast agent in MRI: in vitro study

Abstract: Superparamagnetic cobalt ferrite nanoparticles (CoFe 2 O 4) possess favourite advantages for theranostic applications. Most of previous studies reported that CoFe 2 O 4 magnetic nanoparticles (MNPs) are suitable candidates for induction of hyperthermia and transfection agents for drug delivery. The present study synthesized and investigated the potential use of CoFe 2 O 4 as a contrast agent in magnetic resonance imaging (MRI) by using a conventional MRI system. The CoFe 2 O 4 were synthesized using co-precipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…The analysis indicated a survival rate of more than 50% for the maximum concentration of 0.06 mg/ml. Based on the results of previous studies demonstrated the cytotoxicity of CoFe 2 O 4 nanoparticles of almost 90% for the maximum concentration of 0.75 and 1 mg/ml [ 54 , 55 ], the achieved data represented that the synthesized CoFe 2 O 4 nanoparticles led to concentration-dependent cell death where the enhancement in concentration involved a remarkable reduction in cell proliferation. .…”
Section: Resultsmentioning
confidence: 88%
“…The analysis indicated a survival rate of more than 50% for the maximum concentration of 0.06 mg/ml. Based on the results of previous studies demonstrated the cytotoxicity of CoFe 2 O 4 nanoparticles of almost 90% for the maximum concentration of 0.75 and 1 mg/ml [ 54 , 55 ], the achieved data represented that the synthesized CoFe 2 O 4 nanoparticles led to concentration-dependent cell death where the enhancement in concentration involved a remarkable reduction in cell proliferation. .…”
Section: Resultsmentioning
confidence: 88%
“…However, slightly higher sizes could be optimal for the enhancement of the r 2 relaxivity [ 35 , 36 ]. In addition, the small-sized SPIONs increased the surface-to-volume ratio, and thus the increased dead layer component decreased magnetization ( M S ) [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The optimum concentration of doped-IONPs within a nontoxic concentration range was 0.154 mM reported by Mohammadi et al (2020). 88 These doped-IONPs demonstrate high T2 relaxivity, biodistribution, and long circulation time. 88,90 IONPs doped with transition metal are also employed to minimize the size of superparamagnetic contrast agents while retaining an excellent MRI contrast efficiency.…”
Section: Doped-iron Oxide Nanoparticles (Doped-ionps)mentioning
confidence: 99%
“…88 These doped-IONPs demonstrate high T2 relaxivity, biodistribution, and long circulation time. 88,90 IONPs doped with transition metal are also employed to minimize the size of superparamagnetic contrast agents while retaining an excellent MRI contrast efficiency. 91 A recent study by Nowicka et al (2023) 92 reported magnetic IONPs doped with magnesium have demonstrated outstanding potential for magnetic fluid hyperthermia (MFH) in lung cancer treatments.…”
Section: Doped-iron Oxide Nanoparticles (Doped-ionps)mentioning
confidence: 99%
See 1 more Smart Citation